A computational neuroethology perspective on body and expression perception. Issue 9 (September 2021) - de Gelder, Beatrice; Poyo Solanas, Marta
Abstract : Survival prompts organisms to prepare adaptive behavior in response to environmental and social threat. However, what are the specific features of the appearance of a conspecific that trigger such adaptive behaviors? For social species, the prime candidates for triggering defense systems are the visual features of the face and the body. We propose a novel approach for studying the ability of the brain to gather survival-relevant information from seeing conspecific body features. Specifically, we propose that behaviorally relevant information from bodies and body expressions is coded at the levels of midlevel features in the brain. These levels are relatively independent from higher-order cognitive and conscious perception of bodies and emotions. Instead, our approach is embedded in an ethological framework and mobilizes computational models for feature discovery. Highlights: Body and expression perception may be sustained by midlevel feature computations rather than by body category-selective processes. Body expression coding in the brain may be organized by feature statistics of body posture and movements rather than by natural language semantic categories. Midlevel features at stake in biological computations of body posture and movements exploit ethological characteristics of organism–environment interactions. Midlevel feature processing may on its own sustain rapid expression perception and action preparation, and may not require or depend on computations of the high-order category. Feelings can be associated with midlevel processing and may be precursors to conscious emotional states because they are an intermediate layer between unconscious processes and fully formed conscious emotional states.